2011
DOI: 10.1021/jm201018g
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of Novel Small-Molecule Inhibitors of the Hypoxia Inducible Factor Pathway

Abstract: Hypoxia, a reduction in partial oxygen pressure, is a salient property of solid tumors. Hypoxia drives malignant progression and metastasis in tumors and participates in tumor resistance to radio- and chemotherapies. Hypoxia activates the hypoxia-inducible factor (HIF) family of transcription factors, which induce target genes that regulate adaptive biological processes such as anaerobic metabolism, cell motility and angiogenesis. Clinical evidence has demonstrated that expression of HIF-1 is strongly associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 37 publications
1
51
1
Order By: Relevance
“…19,21 In the current experimental set the IC 50 value of 6e (1.6 μM) was larger than the previous values; this variation might be related to the particular batch of cells used and the smaller number of repeats ( n = 6). Because this compound was used as an internal standard we used the latter value for comparison with the other compounds tested under the same conditions.…”
Section: Figurecontrasting
confidence: 63%
See 1 more Smart Citation
“…19,21 In the current experimental set the IC 50 value of 6e (1.6 μM) was larger than the previous values; this variation might be related to the particular batch of cells used and the smaller number of repeats ( n = 6). Because this compound was used as an internal standard we used the latter value for comparison with the other compounds tested under the same conditions.…”
Section: Figurecontrasting
confidence: 63%
“…1), which showed strong inhibition of reporter activity under hypoxia. 1921 Further testing of 6e revealed that it has potent anti-cancer properties in animal models for brain cancer (glioblastoma), eye cancer (uveal melanoma) and pancreatic cancer (manuscripts in preparation). However, the treatment necessitated delivery of 6e in a formulation, due to poor water solubility (<15 μg/mL; pH7.4), suggesting that further pharmacological optimization is necessary before this family of compounds can be translated to the patient.…”
Section: Introductionmentioning
confidence: 99%
“…In the present context, we define true positives as compounds with an average IC 50 value <650 nM. Five of 30 analogues fall in this category based on the cell-based reporter assay: 648, 306, 478, 378, and 280 nM activity (See Table 10, ref 17).…”
Section: Acs Medicinal Chemistry Lettersmentioning
confidence: 99%
“…Those strategies were mostly aimed at modulation of HIF-1a expression level by compounds affecting its transcription/ translation, 7 compounds activating PHD proteins which promote HIF-1a degradation in a VHL dependent manner, 8 and compounds affecting HIF-1a/ ARNT/p300/CBP complex formation by binding to p300/CBP. 9 Additionally, an RNA antagonist, EZN-2968, composed of a third-generation oligonucleotide, locked nucleic acid technology that specifically binds and inhibits the expression of HIF-1a mRNA was developed and shown to inhibit tumor cell growth in glioblastoma and prostate cancer models. 10 A second HIF isoform, HIF-2a, was identified that is regulated in a manner similar to HIF-1a.…”
Section: Introductionmentioning
confidence: 99%